THE SOCIAL MEANING OF ALANG AS A TRADITIONAL TORAJA RICE GRANARY AND ITS IMPLICATIONS FOR CHARACTER EDUCATION - Simega, Bertin; Harmelia Tulak; Pakiding, Alexander; Sambara, Greis Riani (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
The traditional rice barn of the Toraja community, known as Alang, serves not only as a storage facility for harvested rice but also embodies deeply rooted socio-cultural values that have been transmitted across generations. These social values hold significant potential for strengthening students’ character education. This study aims to uncover the social meanings embedded in Alang and to examine their implications for the development of character education at the elementary school level. The research employed a qualitative approach using an ethnographic study method. Data were collected through interviews, observations, and documentation. The findings indicate that the socio-economic development of Torajan society has led to a transformation in the function of Alang, from a traditional rice storage structure into a symbol of cultural identity and social status. The number of Alang, the motifs of their carvings, and their structural quality signify levels of prosperity and social prestige (customary status). Although some community members no longer store rice in a traditional manner, social values such as siangkaran (mutual cooperation), katuoan (family loyalty), and respect for ancestors continue to thrive within Torajan cultural narratives and have strong implications for character education.